The System Modification of Transmission on The RCWS Prototype UGV Robot (Unmanned Ground Vehicle) - Rendra Dwie Ramadhan; Willem Loe Mau; Rizal Hasbi (Jurnal Otoranpur, 2021)
An automotive transmission system is a system that has the function for conversion torsion and the rapidity (rotation) from the torsion machine and it has a different rapidity to keep on to the last activator. This conversion changes the high rotation speed becomes lower, but it has more energy conversely. The highest torsion in certain machines generally occurs in a half from the limit from the machine rotation which allowed, while the vehicle needs the highest torsion start from it could be moved. The purpose of this study is to modify the accuracy and the exact transmission, so that the activator transmission which uses a pulley system (part of the automobile chassis) and belt will have a gentle rotation by activator use motor stepper with more energy in it. This machine works by having a battery to supply electricity to the motor stepper, then it is controlled by azimuth and elevation moving control so that transmission of weapon bipod will move with elevation-100 s/d 600 degrees. Azimuth moving control will be pressed so it will move the motor stepper and make the weapon move to 360 degrees. The result of the rotation of the motor will move gently and the comparison between use motor DC gearbox which not really soft at the rotation itself.